1985
DOI: 10.1139/v85-162
|View full text |Cite
|
Sign up to set email alerts
|

Mécanisme des réactions du chlorite et du dioxyde de chlore. 3. La dismutation du chlorite

Abstract: R e p le 20 juin 1984 GUY SCHMITZ et HENRI ROOZE. Can. J. Chem. 63, 975 (1985).La dismutation du chlorite a CtC CtudiCe en solutions d'acide perchlorique 0,Ol M a I M, a 25°C et pour une force ionique de 1 M. Les rCsultats impliquent au moins trois processus rCactionnels. Le premier est catalysC par les ions C1-, le second donne une loi d'ordre deux et le troisitme est catalysC par le fer. Sa loi cinCtique est Elle peut Ctre interprktee par la rkaction riversible CIO; + Fe3+ C102 + Fe" suivie de deux Ctapes dk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The net effect of reactions 6, 6′, 7, 7′, and 9 accounts for the unusual chloride ion dependence of the initial rate of decomposition. Our value of k 9 ) 0.00343 M -2 s -1 lies within the previously reported range, which includes determinations of 0.000483, 6 0.0018, 7 and 0.014 5 M -2 s -1 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The net effect of reactions 6, 6′, 7, 7′, and 9 accounts for the unusual chloride ion dependence of the initial rate of decomposition. Our value of k 9 ) 0.00343 M -2 s -1 lies within the previously reported range, which includes determinations of 0.000483, 6 0.0018, 7 and 0.014 5 M -2 s -1 .…”
Section: Discussionsupporting
confidence: 90%
“…Stoichiometry. Several groups of investigators [5][6][7] have found that in the absence of chloride ion the stoichiometry of the decomposition of chlorous acid is given by reaction A:…”
Section: Resultsmentioning
confidence: 99%
“…At neutral and mildly acidic pH, the rate law resembles that of Br(III), with an [H+]-dependent term second-order in C1(III).22 At lower pH, two additional terms appear in the rate law, because HClOz becomes capable of oxidizing C1-to HOCl, giving rise to C1catalysis. 21 The comparable process does not occur for HBr02 in the pH range we have studied, and a similar B r catalysis is not observed. Lastly, an iron-catalyzed radical chain mechanism has been reportedz0 and interpreted as evidence of reversible oneelectron oxidation of ClOz-to C102 by Fe3+; a similar effect has not been observed in the Br(II1) system.…”
Section: Discussionmentioning
confidence: 63%
“…As a consequence, the reaction kinetics will be expected to be different. Also, the impurity effect due to the presence of some transition-metal ions, such as iron, on the disproportionation of chlorous acid, which has been well-documented (Schmitz and Rooze, 1985), may be partly responsible for the difference between these studies.…”
Section: Resultsmentioning
confidence: 95%